Transformasi Pembelajaran Bahasa Indonesia bagi Penutur Asing dalam Meningkatkan Kualitas Hasil Didik - Bambang Nurakhim (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2024)
This transformation aims to produce learning programs that are more adaptive, responsive to the needs of international students, and able to create a comprehensive and in-depth learning experience. With this transformation, it is hoped that foreign speakers will not only learn Indonesian technically, but will also be able to understand and interact with Indonesian culture more broadly. There are many methods and strategies that each teacher can use to make BIPA learning or transformation more effective, both in the process of improving oral and written language skills as well as insight into Indonesian culture. This is the background for the author to conduct research. This is a response and the result of positive values ​​from the various ways language activists and institutions introduce Indonesian to the world. The research method uses a descriptive qualitative approach and literature study. In line with these steps, the Indonesian language learning process organized by the Language Education and Training Center through the Intensive Indonesian Language Course (KIBINA), which is a language transformation process, needs to be explored through comprehensive research, especially efforts to internationalize the Indonesian language in improving the quality of international students' educational outcomes. from time to time. Based on the comparison of the middle and final exam scores, the results can be seen that of the 5 materials that were transformed or taught, 3 of them experienced a decline, such as Listening, Speaking and Grammar skills. The most drastic decline was in listening skills, while the materials that experienced an increase were reading and writing, although the increase was not significant. Based on the findings of researchers in the field, the transformation of knowledge through the Kibina or BIPA program for transformation in the classroom includes 4 (four) skills taught to students, especially foreign students, namely; listening, reading, writing and speaking as well as grammar are required to improve and combine knowledge, affective and psychomotor aspects.